DEVELOPING OF NUMBERS LEARNING MODULE FOR PRIMARY SCHOOL STUDENTS BYCONTEXTUAL TEACHING AND LEARNING APPROACH - Dyah Tri Wahyuningtyas; I Ketut Suastika (STKIP Singkawang, 2017)
This study purposedto develop module of numbers learning by CTL approach. Through CTL strategies, students were expected to learn through 'experience', but not 'memorize'. This module included activities to create a meaningful relationship, presenting a problem in the form of open-ended, problem possing assembling, collaborating, presenting individually services through checking the understanding, and self-assessment. The development model used in this research were divided into three phases: (1) the initial investigation phase (2) the prototype phase, and (3) the assessment phase. The research instrument composed in this study consisted of; (1) questionnaire responses of experts and practitioners, (2) student questionnaire, (3) sheets and questionnaires observation, (4) the test sheet. This development product had fulfilled valid criteria by the achievement of the module validation was 3.31 (high criteria), Observation Students’Activities validation was 3.52 (high criteria), Students’ Questionnaire Response validation was 3.27 (high criteria), and Test Learning Result validation was 3.44 (high criteria). Based on the validation results, it could be concluded that the module and instrument which were developed was valid.